Improved Composting Through Fermented Activators - Pascual, Pet Roey L. (JPAIR Multidisciplinary Research, 2013)
Composts are important components in improving or restoring soil fertility. However, it takes long time for it to prepare and buying starter cultures of beneficial microorganisms to speed-up composting can be expensive. Thus, a study was conducted to quantify microorganisms from the different fermented activators and EM using PCA, determine the duration of compost maturity, percent recovery of compost, and nutrient content and pH of compost as affected by different fermented activators and EM. Significant lower temperature were registered on the compost (30% Browns + 30% Greens + 40% Banana Bract) applied with commercial effective microorganism (EM) from five to eight weeks of composting than those applied with fermented activators and tap water. Such is a sign of earlier maturity. Meanwhile, application of Fermented Swamp Cabbage Juice alone improved the percent recovery of compost by 0.36 times (46.70%) compared to those applied with tap water only (34.33%).
Keywords: agriculture; composting; fermented activators; experimentalesearch; Philippines